DEVELOPMENT OF STROKE AMONG THE POPULATION >18-90 YEARS OF AGE AGAINST THE BACKGROUND OF AIR TEMPERATURE FLUCTUATIONS IN THE CLIMATIC CONDITIONS OF SOUTHERN KYRGYZSTAN (American Journal of Technology and Applied Sciences, 2023)
Over the past decades, the unprecedented rate of global warming and climate change has been a source of concern. In recent years, climate change has been considered as one of the leading factors influencing public health and the formation of acute and chronic non-communicable diseases. The Fergana Valley of Kyrgyzstan belongs to a different climatic and geographical zone. Residents of the plains and low-mountain regions of southern Kyrgyzstan are more adapted to a hot climate, the effect of which on their health has not been studied using new WHO methodological approaches.